Transforming Vocational Learning with Interactive Multimedia: Creative Solutions for the Digital Era - Elga Elfira; Ramalis Ramalis; Jasrial Jasrial; Rayendra Rayendra (Jurnal Penelitian Pendidikan IPA, 2025)
The use of interactive multimedia in learning is expected to stimulate students' interest and encourage greater involvement in the learning process, given that some students often find the material difficult and abstract. This research aims to develop interactive multimedia in subjects in class X of SMK Negeri 6 Padang, which is focused on Computing Systems material. This research involves the stages of analysis, design, development, and evaluation to produce valid, practical, and effective learning media. The validation results showed that the interactive multimedia developed had a very high level of validity, with scores reaching 100% from media, material, and language experts. The practicality test on teachers and students also showed very positive results, with an average score of 95%, which indicates that this medium is very practical to use in learning. The effectiveness of the media was measured through the pretest and posttest, with results showing an increase in student understanding, with an average N-gain score of 67.58%, which was categorized as "moderate". In conclusion, the interactive multimedia developed can be used as a valid, practical, and effective learning medium to improve students' understanding of subjects at vocational schools. This research makes an important contribution to the development of technology-based learning media at the secondary education level.